Prevalence and Associated Factors of Geriatric Syndromes Among Older Adults in Southern Kyrgyzstan - Medina Zheenbaeva, Amanai Kadyrbaeva, Sagynali Mamatov, Mira Arstanbekova, Diana Smailova, Merim Murzaibragimova, Chynara Kasymbaeva, Gilbera Romankulova, (Asian Journal of Pharmaceutics (AJP), 2025)
Geriatric syndromes (GSs) are complex clinical conditions that significantly affect morbidity and mortality in older adults. This cross-sectional study aimed to evaluate the occurrence of GSs and determine the factors associated with multiple GSs among 570 older adults aged 65–94 years in the southern region of the Kyrgyz Republic. Methods: Participants underwent a comprehensive geriatric evaluation to examine frailty syndrome, depression, malnutrition, orthostatic hypotension, urinary incontinence, fecal incontinence, cognitive impairment, basic dependence in daily activities, falls, visual impairment, hearing impairment, sensory deficits, and chronic pain syndrome. Results: 90.4% of the participants had at least one GS, with 76.2% experiencing two or more. The most prevalent GSs were visual and hearing impairment, chronic pain syndrome, dependency in daily life, cognitive impairment, depression, urinary incontinence, malnutrition, and risk of malnutrition. The prevalence of frailty syndrome was 25.2%, whereas pre-frailty was observed in 31.5% of the cases. Factors associated with frailty syndrome included being female, older age, poor socioeconomic conditions, living alone, and lower levels of education. Oral health evaluation revealed a high prevalence of periodontal disease, bone loss, and edentulousness. Conclusion: The findings highlight the need for comprehensive geriatric evaluation, collaborative care models, and preventive measures in primary healthcare to reduce the impact of geriatric conditions and improve the quality of life of Kyrgyzstan’s elderly population